Inspiring respect for fathers as coparents through a trauma-informed, infant-family mental health transformation of community-based services: process and early implementation with a multi-agency community collaborative - McHale, James; Burton, Donna; Negrini, Lisa; Jacob, Alexandra Albizu; Butler, LaDonna (Frontiers in Psychology, 2023)
Helping communities become more proactive in the implementation of agency services that deliver trauma-informed, family-centered (TI-FC) care aid in the promotion of stronger, more engaged, and healthier fathers and families. The current case study details the establishment of a transformational effort at the community level in which major health, mental health, substance abuse, and child welfare organizations serving families of children birth to age worked collaboratively to enhance their TI-FC services. We describe a four-stage process detailing the work of the collaborative, which was guided by key agency administrators and decision-makers. In stage 1, lead administrators took part in a 5-month planning phase to define terms, objectives and scope of the initiative, agree on a common set of commitments, plan communications with agency personnel and concretize a strategy for regularly reviewing progress. In stage 2, an organizational readiness assessment stage, multi-agency staff completed anonymous surveys addressing TI-FC care within their organizations; focus groups provided detailed information about staff experiences with the implementation of TI-FC strategies; and agencies provided for review common public documents describing the nature of their programs and service activities - particularly as related to TI-FC care. In stage 3, readiness data were collated to create partner organizational profiles that were shared with agency leadership as a baseline against which later post-transformational change could be compared. In stage 4, all front-line staff, managers, and supervisors participated in a training series for multi-agency staff covering TI-FC practices and reflective supervision and practice. This report details the planning process, TI-FC training series, and organizational profile assessments. We conclude with recommendations regarding the establishment of multi-agency collectives to include fathers toward betterment of infant-family mental health at a community level.